Cold agglutinin-induced hemolytic anemia during room temperature fluid resuscitation: a case report - Yosuke Kawai; Miyoshi Deguchi; Naoko Mizouchi; Satoru Yoshida; Ken Kumagai; Yasuo Hirose (Journal of Medical Case Reports, 2021)
Abstract Background Cold agglutinin disease can cause the agglutination of red blood cells and hemolytic anemia due to cold temperature. Herein, we report a case of progressive hemolytic anemia due to cold agglutinin disease during fluid resuscitation and in the absence of exposure to cold. Case presentation A 71-year-old Japanese man was admitted to the emergency department with signs of hypotension and disturbed consciousness. He was diagnosed with diabetic ketoacidosis, and treatment with fluid resuscitation and insulin infusion was initiated. Laboratory test results obtained the following day indicated hemolytic anemia. On day 5 after admission, red blood cell agglutination was detected, and the patient was diagnosed with cold agglutinin disease. Conclusions Cold agglutinin disease should be considered in the differential diagnosis of progressive hemolytic anemia during fluid resuscitation, even if the solution is at room temperature.